2020
DOI: 10.25273/jipm.v8i2.5048
|View full text |Cite
|
Sign up to set email alerts
|

Beginner Teacher's Perception of Application of Project-Based Learning in Mathematics Learning

Abstract: <p class="JRPMAbstractBody">This research aims to describe the teacher's perception of the application of project-based learning in mathematics learning and how they will apply it using a qualitative case study method. The research subjects in this study amounted to 12 students consisting of 3 men and 9 women, where they were students of post-graduate mathematics education study programs at Yogyakarta State University who were beginner teachers where they had taught between 1 and 3 years. Data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…However, many educators consider that adopting PjBL still faces several challenges. Among these is a study by Guntur and Retnawati (2020). This study revealed that respondents have positive perceptions of project-based learning; however, most of them lack knowledge and experience with it; consequently, they will encounter obstacles in implementing it, and there is a need for additional research on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…However, many educators consider that adopting PjBL still faces several challenges. Among these is a study by Guntur and Retnawati (2020). This study revealed that respondents have positive perceptions of project-based learning; however, most of them lack knowledge and experience with it; consequently, they will encounter obstacles in implementing it, and there is a need for additional research on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Persepsi sendiri adalah pandangan atau pendapat yang berperan dalam menentukan pengambilan keputusan seorang (Guntur & Retnawati, 2020). Sehingga persepsi guru akan sangat penting dalam proses belajar mengajar, karena akan menjadi panduan guru dalam bersikap dan mengambil keputusan di kelas.…”
Section: Giving Examples In Mathematics Teaching Is Something That Is...unclassified